Improving the Allocation of Indirect Costs Using the FABC Method (Based on the Example of a Paper and Cardboard Manufacturing Company) - Liubinaitė, Ermina; Lipskytė, Ieva (Buhalterinės apskaitos teorija ir praktika, 2023)
Every enterprise seeks to determine as accurately as possible the cost of the products or services it produces. The allocation of indirect costs causes considerable difficulties in this process. In the search for the most accurate alternatives for allocating indirect costs, the Activity Based Costing (ABC) method has become more popular in recent decades and is increasingly used by companies. The ABC method has many advantages, but it also has disadvantages, which have led to further development of the method by proposing newer versions. These include Fuzzy Activity Based Costing (FABC), which reduces the risk of uncertainty in data collection conditions and inaccurate cost allocation. However, while the literature provides a theoretical model of the FABC approach, there is very little research focused on sector-specific companies. Given that the issue of indirect cost allocation is particularly relevant for manufacturing companies, this paper explores the possibilities of applying the FABC method in manufacturing companies, using the example of a paper and cardboard manufacturing company. The aim of the research: after revealing the principles of ABC and FABC implementation, to improve the indirect cost allocation process in a paper and cardboard manufacturing company using the FABC method. The methods used for the study were document analysis, observation, conversation, interview, and fuzzy set analysis. The results showed that the FABC method has lower cost drivers for some activities and higher cost drivers for others than the ABC method. The improvement path developed for the allocation of indirect costs using the FABC approach could serve as a good model for its implementation in other manufacturing sectors.